KEANEKARAGAMAN AVIFAUNA DIURNAL PADA KAWASAN MEMPAWAH MANGROVE PARK DAN SEKITARNYA DI DESA PASIR KABUPATEN MEMPAWAH - Prabowo, Apik; Dewantara, Iswan; Prayogo, Hari (JURNAL HUTAN LESTARI, 2019)
Avifauna is one of the animals that is easily found in various places, and is one indicator of environmental quality. Avifauna has the ability to spread seeds, help pollinate, natural predators of other animals, and others. This study aims to record the diversity of diurnal avifauna in area Mempawah Mangrove Park and its surroundings in Pasir Village Mempawah Hilir Subdistrict, Mempawah district. The research method used the Point count method, whose observation points are obtained by Purposive sampling, carried out on 9 July-9 August 2018. The results of observations were 35 species of avifauna consisting of 24 families which were divided into three habitats, in the mangrove habitat there were 18 species and 15 families, mixed garden contained 22 species and 18 families, and rice field contained 17 species and 11 families. The dominance index in the mangrove habitat is C = 0.40, mixed garden is C = 0.10 and rice is C = 0.13, indicates that no species dominates the other species, meaning the role of the avifauna species found in all three same habitat. Diversity index shows that mixed garden habitat has a higher species diversity with () = 2.66, mangrove habitat is () = 2.43 and a rice field habitat is () = 2.40, indicates that the three habitats have diversity with moderately criteria. Evenness index in mangrove habitat is (E) = 0.84, in mixed garden habitat is (E) = 0.85 and a rice field habitat is (E) = 0.85, indicates the three habitats the abundance includes evenly distributed or included in a stable community. The highest similarity index of avifauna species is between mangrove habitat and mixed garden with a percentage of 53.58%, rice field habitat with a garden with a percentage of 53.19%, and mangrove habitat with rice fields with a percentage of 38.49%. The highest similarity was between.Keywords: Avifauna, Diversity, Mempawah Mangrove Park